Stabilization and Structural Reform in the Czech and Slovak Federal Republic : First Stage - Aghevli, Bijan (Occasional Papers; Occasional Paper, 1992)
On January 1, 1991, the Czech and Slovak Federal Republic launched a comprehensive reform program designed to establish a market economy. This paper charts the progress of the reform program in the context of Czechoslovakia's prewar history as a major industrial power, its subsequent slow economic decline under Communism, and its recent integration into the world economy following the collapse of the Council for Mutual Economic Assistance.